Inhibition of Connective Tissue Growth Factor Ameliorates Disease in a Murine Model of Rheumatoid Arthritis. Issue 6 (30th May 2013) - Nozawa, Kazuhisa; Fujishiro, Maki; Kawasaki, Mikiko; Yamaguchi, Ayako; Ikeda, Keigo; Morimoto, Shinji; Iwabuchi, Kazuhisa; Yanagida, Mitsuaki; Ichinose, Shouzo; Morioka, Megumi; Ogawa, Hideoki; Takamori, Kenji; et al.
<x xml:space="preserve">Abstract</x> Objective We have shown that connective tissue growth factor (CTGF) plays an important role in the pathogenesis of rheumatoid arthritis (RA). This study was undertaken to evaluate the effects of blockade of the CTGF pathway on the development of collagen‐induced arthritis (CIA) in mice. Methods Arthritis was induced in DBA/1J mice by immunization with a combination of type II collagen (CII) and Freund's complete adjuvant. We evaluated the development of arthritis in mice with CIA left untreated versus treated with neutralizing anti‐CTGF monoclonal antibody (mAb). Results Inhibition of CTGF in mice treated with neutralizing anti‐CTGF mAb significantly ameliorated arthritis compared to the untreated mice with CIA. Serum levels of matrix metalloproteinase 3 were reduced by anti‐CTGF mAb treatment. Moreover, blockade of CTGF decreased interleukin‐17 expression on purified CD4+ T lymphocytes. Although the expression of the retinoic acid receptor–related orphan receptor γt gene was not suppressed by anti‐CTGF mAb treatment, that of interferon regulatory factor 4 (IRF‐4) and IκBζ (Nfkbiz), which are other important molecules for the differentiation of Th17 cells, was suppressed. In addition, blockade of CTGF inhibited pathologic proliferation of T lymphocytes in response to CII restimulation in vitro. Moreover, aberrant osteoclastogenesis in mice with CIA was restored by anti‐CTGF mAb treatment. Conclusion Our findings indicate that blockade of CTGF prevents the progression of arthritis in mice with CIA. Anti‐CTGF mAb treatment suppresses pathologic T cell function and restores aberrant osteoclastogenesis in mice with CIA. CTGF may become a new target for the treatment of RA.